Análises da dinâmica orçamentária dos municípios brasileiros: Uma aplicaç\~ao da metodologia var com dados emphilhados - Bernardo Patta Schettini (Instituto de Pesquisa Econômica Aplicada (IPEA), 2012)
– The paper estimates a panel-VAR using data on total expenditures, tax receipts and overall grants received for 5.544 Brazilian municipalities observed from 2002 through 2010. A sequence of hypotheses was investigated by the means of overidentification test statistics. Among our main findings, we underscore there exists evidence of change in the fiscal behavior of the municipalities, but which in average support the tax and spend hypothesis, as well as the flypaper effect of grants over expenditures. We also find there is a lot more dynamics in the expenditure compared to own revenues. We believe these results shed light on some important aspects of the municipal budget dynamics.
Keywords: C12; C33; H72; 330